Neonatal polycythaemia - Bashir, Bashir Abdrhman (Sudan J Paediatr, 2019)
Neonatal polycythaemia has multifactorial causes, and can be designated as active (increased foetal erythropoiesis) or passive (red blood cell transfusion) polycythaemia. Hematocrit estimated from capillary blood (regularly obtained through “heel sticks” in newborns) is normally the principal laboratory feature facility by which polycythaemia is recognszed. An unusually high proportion of haematocrit builds the risk of hyperviscosity, microcirculatory hypoperfusion, and in the long run multisystem organ dysfunction. A report enclosed in this short communication gives a brief review of neonatal polycythaemia, its causes, management and complications.